The Gilded Age and Progressive era : a historical exploration of literature - Martin, Wendy, 1940-; Tichi, Cecelia, 1942- (Santa Barbara, California : Greenwood, 2016)
"This book offers a one-stop reference work covering the Gilded Age and Progressive era that serves teachers and their students. Integrates and aligns material for American literature and social studies curricula. Offers a range of tools to support literary works--analysis, history, document excerpts, and areas for study. Provides historical context for multiple key works of literature on the Gilded Age and Progressive era"--
"The Historical Explorations of Literature series is designed to help students to understand key works of American literature by putting them in the context of history, society, and culture through historical context essays, literary analysis, chronologies, primary source documents, and suggestions further research. Each volume in the series covers four or five canonical works related to a particular area of American literature--significant literary productions of the Jazz Age or the Harlem Renaissance, for example. For each title covered, students will find a brief synopsis of the work; separate essays on the work's historical background and the author's biographical background; an essay on "Why We Read This Work," summarizing the work's enduring value and significance; and a series of thematic "Historical Explorations" that include a selection of related primary documents"--
Part I: The Gilded Age -- 1. A Connecticut Yankee at King Arthur's Court (Mark Twain, 1889) -- 2. "The Yellow Wallpaper" (Charlotte Perkins Gilman, 1892) -- Part II: The Progressive Era -- 3. The Jungle (Upton Sinclair, 1906) -- 4. A Lost Lady (Willa Cather, 1924).
Includes bibliographical references and index.
Keywords: American literature -- 19th century -- History and criticism; American literature -- 20th century -- History and criticism; Literature and history -- United States -- History -- 19th century; Literature and history -- United States -- History -- 20th century; United States -- Intellectual life -- 19th century; United States -- Intellectual life -- 20th century